1976
DOI: 10.1159/000114744
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Long-Term L-Dopa Therapy on Carbohydrate Metabolism in Patients with Parkinson’s Disease

Abstract: Carbohydrate metabolism and insulin secretion were investigated in 26 patients with Parkinson’s disease before and during L-dopa treatment. Oral glucose tolerance tests were performed on 13 patients treated with L-dopa alone and on 7 patients treated with L-dopa combined with Carbidopa. Intravenous glucose tolerance tests were performed on additional 6 patients treated with L-dopa alone. Results indicate that chronic L-dopa administration does not modify glucose metabolism. It was observed only a significant d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0
1

Year Published

1989
1989
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 0 publications
1
20
0
1
Order By: Relevance
“…Interestingly, pancreatic β cells also express dopamine receptors and treatment with the selective D 2 R agonist quinpirole causes the inhibition of glucose-stimulated insulin secretion [80]. In rodents, a single injection with the dopamine precursor L -dopa results in inhibited insulin secretory response [81,82], whereas treatment with L -dopa in humans suffering from Parkinson's disease reduces insulin secretion upon a glucose load [83]. FG and insulin, as well as HOMA-IR, have been found significantly ameliorated also in patients with Cushing's disease following a 24-month treatment with CAB after unsuccessful surgery [84].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, pancreatic β cells also express dopamine receptors and treatment with the selective D 2 R agonist quinpirole causes the inhibition of glucose-stimulated insulin secretion [80]. In rodents, a single injection with the dopamine precursor L -dopa results in inhibited insulin secretory response [81,82], whereas treatment with L -dopa in humans suffering from Parkinson's disease reduces insulin secretion upon a glucose load [83]. FG and insulin, as well as HOMA-IR, have been found significantly ameliorated also in patients with Cushing's disease following a 24-month treatment with CAB after unsuccessful surgery [84].…”
Section: Discussionmentioning
confidence: 99%
“…One can speculate that changes in dopamine levels might generate multiple responses, allowing coordination of feeding behaviors together with regulation of pancreatic endocrine and exocrine functions. Interestingly, treatment with L-dopa alters insulin secretion in patients with Parkinson disease (10,57,58). Moreover, antipsychotic (neuroleptic) drugs blocking dopamine receptors may cause hyperinsulinemia (59), hypoglycemia (60), increase appetite, and obesity (61,62) and are associated with diabetes (61,63,64).…”
Section: Discussionmentioning
confidence: 99%
“…Treatment with dopamine precursor L-dopa in humans suffering from Parkinson disease reduces insulin secretion upon oral glucose tolerance test (10). In rodents, a single injection with L-dopa results in the accumulation of dopamine in beta cells and inhibition of the insulin secretory responses (11,12).…”
mentioning
confidence: 99%
“…Sandyk et al [23] reported impaired glucose tolerance in 50-80 % of patients with PD whom they studied and concluded that levodopa treatment aggravated it. Other authors, however, have reported that levodopa did not impair glucose tolerance [22] nor enhance plasma insulin and glucose concentration levels [24]. Davies et al [6] postulated that weight loss in PD patients is due to an increased metabolic rate or altered muscle metabolism.…”
Section: ■ Increased Energy Metabolismmentioning
confidence: 99%